Strengthening strategic management approaches to address antimicrobial resistance in global human health: a scoping review - Ahmad,R; Zhu,NJ; Leather,AJM; Holmes,A; Ferlie,E (BMJ Global Health, 2019)
Introduction: The development and implementation of national strategic plans is a critical component towards successfully addressing antimicrobial resistance (AMR). This study aimed to review the scope and analytical depth of situation analyses conducted to address AMR in human health to inform the development and implementation of national strategic plans. Methods: A systematic search of the literature was conducted to identify all studies since 2000, that have employed a situation analysis to address AMR. The included studies are analysed against frameworks for strategic analysis, primarily the PESTELI (Political, Economic, Sociological, Technological, Ecological, Legislative, Industry) framework, to understand the depth, scope and utility of current published approaches. Results: 10 studies were included in the final review ranging from single country (6) to regional-level multicountry studies (4). 8 studies carried out documentary review, and 3 of these also included stakeholder interviews. 2 studies were based on expert opinion with no data collection. No study employed the PESTELI framework. Most studies (9) included analysis of the political domain and 1 study included 6 domains of the framework. Technological and industry analyses is a notable gap. Facilitators and inhibitors within the political and legislative domains were the most frequently reported. No facilitators were reported in the economic or industry domains but featured inhibiting factors including: lack of ring-fenced funding for surveillance, perverse financial incentives, cost-shifting to patients; joint-stock drug company ownership complicating regulations. Conclusion: The PESTELI framework provides further opportunities to combat AMR using a systematic, strategic management approach, rather than a retrospective view. Future analysis of existing quantitative data with interviews of key strategic and operational stakeholders is needed to provide critical insights about where implementation eff